Alamandine reduces leptin expression through the c-Src/p38 MAP kinase pathway in adipose tissue - Uchiyama, Tsuyoshi; Okajima, Fumikazu; Mogi, Chihiro; Tobo, Ayaka; Tomono, Shoichi; Sato, Koichi (PLOS ONE, 2017)
Objective Obesity is associated with an increased risk of diabetes mellitus, hypertension, and renal dysfunction. Angiotensin 1–7 and alamandine are heptameric renin angiotensin system peptide hormones. Further, alamandine levels increase with renal dysfunction. In the cardiovascular system, angiotensin 1–7 and alamandine produce similar improvements and counterbalance angiotensin II in regulating vascular function. We aimed to determine whether the effect of alamandine on leptin expression and secretion in adipocytes was similar to that of angiotensin 1–7. Approach and results We studied isolated peri-renal visceral adipose tissue and peri-renal isolated visceral adipocytes from male Wistar rats. Angiotensin II from 0.01 to 10nM had no effect on leptin expression. Angiotensin 1–7 (1 nM) increased leptin secretion and expression, whereas alamandine (1 nM) decreased leptin secretion and expression in adipose tissue and isolated adipocytes and reduced blood leptin levels in vivo. These effects were mediated by Gq, c-Src, p38 mitogen-activated protein, and IκB activation. Additionally, alamandine induced nitric oxide expression via inducible nitric oxidase synthase and plasminogen activator inhibitor 1 expression in adipose tissue and isolated adipocytes. Conclusions Angiotensin 1–7 and alamandine produced opposing effects on leptin expression and secretion in adipose tissue. This result suggests that the action of Mas (angiotensin 1–7 receptor) and Mas-related G-protein coupled receptor D in adipocytes exhibited opposing actions similar to angiotensin II type 1 and type 2 receptors.